Glutathione‐Responsive Near‐Infrared‐II Fluorescence Probe for Early and Accurate Detection of In Situ and Metastatic Tumors - Yin, Likun; Xu, Pu; Huang, Yuxin; Gu, Xuxuan; Sun, Liwen; Zhou, Hui; Zhou, Wen; Xie, Chen; Fan, Quli (Small (Weinheim an der Bergstrasse, Germany), 2025)
In situ and metastatic malignant tumors are primary diseases that threaten human life. Among all the metastases, liver metastasis is the most difficult to detect. As most imaging probes have high liver accumulation, it is difficult to distinguish tiny metastases from normal liver tissue with strong background signal. In this study, the design of a novel second near‐infrared window (NIR‐II) fluorescence probe for precise detection of carcinoma in situ and liver metastases is presented. The probe called Tg‐RGD utilizes a commercially available cyanine dye IR‐806 as the signaling moiety, a disulfide bond linker as the responsive moiety, an RGD‐capped poly(ethylene glycol) (PEG) as the water soluble enhancer, and the tumor targeting moiety. Tg‐RGD shows good glutathione (GSH) responsiveness and selectivity, where its NIR‐II fluorescence intensity can enhance 50‐fold after activation. In vivo study indicates that Tg‐RGD shows much better imaging and targeting effects than Tg‐PEG with a similar structure but without RGD moiety for both orthotopic breast cancer and osteosarcoma. Most importantly, Tg‐RGD can detect tiny liver metastases with high signal‐to‐background ratio (3.2). Thus, this study reports a high‐performance tumor‐specific NIR‐II fluorescence probe for in situ and tiny metastatic tumor detection, and may further broaden the applications into related tumor lesions. A glutathione‐responsive second near‐infrared window (NIR‐II) fluorescence probe enables precise detection of in situ tumors and liver metastases is designed. Such a probe is composed of a cyanine dye‐based backbone, a glutathione (GSH)‐responsive linker, and an RGD‐capped poly(ethylene glycol) PEG. It can effectively target tiny tumor tissue and turn on its NIR‐II fluorescence signal in the presence of tumor overexpressed GSH.